2009
DOI: 10.1177/1352458509104595
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 autoimmune syndrome and anti-aquaporin-4 antibody-negative opticospinal multiple sclerosis in Japanese

Abstract: Anti-AQP4 antibody-positive patients are immunologically distinct from anti-AQP4 antibody-negative OSMS patients owing to a Th2 shift in the former group in comparison to a Th1 shift in the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 38 publications
10
69
1
Order By: Relevance
“…In a French study, Marignier and colleagues reported that there was no difference between NMOIgG sero-positive and sero-negative NMO patients according to their clinical, CSF, and imaging features 14 . However, in the Japanese, AQP4 antibody-positive NMO/OSMS patients had a greater frequency of longitudinally extensive spinal cord or brain lesions than did anti-AQP4 antibody-negative NMO/OSMS patients 9,[15][16][17] . These discrepancies may be accounted for by patient selection (NMO versus OSMS patients; different populations) and false-negative findings because of the low sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In a French study, Marignier and colleagues reported that there was no difference between NMOIgG sero-positive and sero-negative NMO patients according to their clinical, CSF, and imaging features 14 . However, in the Japanese, AQP4 antibody-positive NMO/OSMS patients had a greater frequency of longitudinally extensive spinal cord or brain lesions than did anti-AQP4 antibody-negative NMO/OSMS patients 9,[15][16][17] . These discrepancies may be accounted for by patient selection (NMO versus OSMS patients; different populations) and false-negative findings because of the low sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 88%
“…A previous study suggested that the presence of AQP4 antibodies was 33-91% sensitive (median 63%) and 85-100% specific (median 99%) for NMO 9 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Amongst Hong Kong Chinese, 60% seropositivity was reported. 106,108,135,139 In a mixed Asian and European Turkish population, sensitivity was 45%. 109 A lower rate of seropositivity (33%) was reported in the Caribbean area, where NMO patients are of predominantly African ancestry, 60 whereas in Spanish, Italian and French populations of Europe, and Brazilian cohorts, seropositivity more frequently corresponded to Caucasian data (41-64%).…”
Section: Brain Mrimentioning
confidence: 98%
“…4,26,61,110 Anti-AQP4 antibody-positive Japanese patients with optico-spinal MS (OSMS) might be immunologically different from antibody-negative OSMS patients. 135 The NMO-IgG ⁄ anti-AQP4 seropositivity rate widely varied according to ethnicity. The sensitivity of the original indirect immunofluorescent method detecting NMO-IgG in Caucasian populations is 42-78%, whereas specificity is 91-100%.…”
Section: Brain Mrimentioning
confidence: 99%